PROVIDING DIPLOMATIC PROTECTION OF CITIZENS - Панахова, Есмер Агіл кизи (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Goal: identifying features of providing diplomatic protection of citizens. Methods of research: analysis and study of international legal documents containing provisions on the diplomatic protection of citizens. Results: the institution of diplomatic protection is based primarily on the customary rules of international law. In accordance with the doctrine of international law, the damage caused to a person is damage to his state, and the state, exercising diplomatic protection, primarily defends its own rights. Diplomatic protection, above all, is a means of ensuring compliance with the regime of foreigners in relation to the person or persons. It is generally accepted that diplomatic protection can be exercised, as a rule, only by the state of citizenship of an individual. It should be noted that in the exercise of diplomatic protection, many problems arise in connection with citizenship. The principle of effective citizenship with diplomatic protection is of considerable interest, since the legal connection between citizenship between the protected state and the state can be quite weak if, with respect to citizens, some compulsory diplomatic protection is recognized, the provision of the same protection against refugees and stateless persons depends on the discretion of the state. Discussion: the proposal to include this issue on the agenda of international organizations. The exercise of diplomatic protection is governed mainly by international customary law. States treat different aspects of diplomatic protection differently. The Institute of Diplomatic Protection of Citizens currently continues to be based primarily on the norms of international legal customs. In developing the draft articles on diplomatic protection in the framework of the UN International Law Commission, besides codification, the progressive development of the norms of the institute of diplomatic protection with regard to citizenship issues was also achieved. First, a person with dual or multiple citizenship may claim protection from the states whose citizenship he has from the actions of the state of which the person is also a citizen, based on the criterion of prevailing citizenship (i.e. effective citizenship), number and on joint protection, against a third state, a citizen of which this person is not. Secondly, stateless persons and refugees were able to turn to the diplomatic protection of the states in whose territory they legally and usually live, given that such residence must take place both at the time of their injury and at the time of the official presentation of claims about causing it. Thus, the adoption of a universal convention based on the Draft Articles on Diplomatic Protection developed by the UN International Law Commission in 2006 will contribute to the codification and progressive development of the international legal regulation of the institution of citizenship.